2011
DOI: 10.1016/j.jval.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life after Total Knee Replacement or Unicompartmental Knee Arthroplasty in an Urban Asian Population

Abstract: Both TKR and UKA patients experienced significant improvements in HRQoL, particularly in the role physical and pain domains. After controlling for potential confounding variables, the type of surgery was not a significant predictor of patients' postoperative HRQoL scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…The score of each subcategory was converted to a scale of 0−100, with a higher score indicating better health2, 14 ) . The Western Ontario and McMaster Universities Arthritis Index (WOMAC) was used, along with the SF-36, as tools to evaluate knee function and the patients’ quality of life15 ) . It is comprised of a total of 24 subcategories under the key categories of pain, stiffness, and physical function.…”
Section: Methodsmentioning
confidence: 99%
“…The score of each subcategory was converted to a scale of 0−100, with a higher score indicating better health2, 14 ) . The Western Ontario and McMaster Universities Arthritis Index (WOMAC) was used, along with the SF-36, as tools to evaluate knee function and the patients’ quality of life15 ) . It is comprised of a total of 24 subcategories under the key categories of pain, stiffness, and physical function.…”
Section: Methodsmentioning
confidence: 99%
“…A minimum followup of 6 months was required. The minimum time was chosen owing to evidence indicating that improvement at 6 months has been shown to be an approximation for improvement at 12 months [22,29,43] and 24 months [40]. Studies that reported results of TKA together with other types of replacement surgery, including THA or unicompartmental knee arthroplasty, were included if the data for TKA outcomes could be isolated.…”
Section: Methodsmentioning
confidence: 99%
“…The aging of the population is likely to raise demand for both primary total hip arthroplasty and revision procedures (Birrell, Johnell, & Silman, 1999;Rissanen et al, 1997;Williams et al, 1994). With the increasing focus on patient-reported outcomes, such as functioning and quality of life, numerous PROMs have been developed to measure procedure outcomes (Ethgen, Bruy ere, Richy, Dardennes, & Reginster, 2004). With the increasing focus on patient-reported outcomes, such as functioning and quality of life, numerous PROMs have been developed to measure procedure outcomes (Ethgen, Bruy ere, Richy, Dardennes, & Reginster, 2004).…”
Section: Methodsmentioning
confidence: 99%